FC 131OFATUMUMAB OR RITUXIMAB FOR CHILDREN WITH STEROID-DEPENDENT NEPHROTIC SYNDROME. A RANDOMIZED CONTROLLED TRIAL. (29th May 2021) - Ravani, Pietro; Colucci, Manuela; Bruschi, Maurizio; Vivarelli, Marina; Cioni, Michela; Di Donato, Armando; Cravedi, Paolo; Lugani, Francesca; Emma, Francesco; Angeletti, Andrea; Ghiggeri, Gian Marco
Abstract: Background and Aims: The chimeric anti-CD20 monoclonal antibody rituximab has been successfully used in steroid-dependent forms of nephrotic syndrome (SDNS) to maintain oral-drug-free remission, but relapses at one year occur in almost half of the patients. Ofatumumab, a fully human anti-CD20 monoclonal antibody, may be superior to rituximab in maintaining remission of SDNS. We compared the efficacy and safety of ofatumumab vs. rituximab in children and young adults with SDNS (NCT02394119) and evaluated the risk of relapse following steroid and calcineurin-inhibitor tapering and withdrawal. Method: We randomly assigned 140 children and younger adults (age 2-24 years) with SDNS maintained in remission with steroids and calcineurin-inhibitors to receive intravenous ofatumumab (1.500 mg/1.73 m2; intervention) or rituximab (375 mg/m2; control). Following infusions, oral drugs were tapered and withdrawn. Participants were followed for 24 months. The primary outcome was relapse at one year, defined by protein-creatinine ratio ≥2000 mg/g or >3+ protein on urine dipstick for 3 consecutive days. Cellular and safety data were also assessed. Results: At 12 months, 36 patients (51.4%) relapsed in the rituximab arm and 37 (52.8%) in the ofatumumab arm (Odds Ratio [OR] 1.06; 95% confidence interval [CI] 0.55 to 2.06). At 24 months, 46 children relapsed in the rituximab arm (65.7%) and 53 in the ofatumumab arm (75.7%). In both arms, circulating B cell levels declined following treatment and recovered between 3 and 9 months. Higher pretreatment levels and faster recovery after decline of memory B cells predicted relapse. Conclusion: In children and younger adults with SDNS, ofatumumab is not superior to the chimeric anti-CD20 antibody rituximab. Immune phenotyping data indicate that anti-CD20 therapies alter the course of the disease by interfering with memory B cell populations and can be used to predict response to anti-CD20 treatment.